Transfers and Implementations of a Swedish Manual Work Program: Sloyd and Entrepreneurial Power - Lawn, Martin (Swiss Journal of Educational Research, 2018)
Sloyd, a Swedish handwork programme for schools, beginning in the late years of the 19th century, was influential in Sweden but almost immediately it began to influence teachers and educators from other countries. This influence is explored in this paper. Using transnational historiography, the sites of influence, and the flow of people and texts, is explored. The focus here is on the circulations of ideas and practices between states, and in particular, between Sweden, the US, the UK and India, and the particular ways in which this flow and embedding of Sloyd occurred.The paper is about Sloyd and about the conditions underlying its influence in other countries, broadly from the 1890s to the 1930s, although its effects continued to roll out across the world after this period.